2015
DOI: 10.1109/lsp.2015.2447934
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Construction of Compressed Sensing Matrices from Protograph LDPC Codes

Abstract: This letter considers the design of measurement matrices with low complexity, easy hardware implementation and good sensing performance for practical compressed sensing applications. We construct a class of sparse binary measurement matrices from protograph Low-density parity-check (LDPC) codes, which can satisfy these features simultaneously. The optimal performance of proposed matrices is analyzed from the mutual coherence aspect. Moreover, we obtain a sufficient condition for optimal construction of the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Both RIP [16][17][18][19] and coherence [9][10][11][12][13][20][21][22][23][24][25][26][27] are important tools to analyze the property of measurement matrices. In this paper, coherence will be adopted to analyze and illustrate the property of constructed measurement matrices, because it is easier to compute.…”
Section: Lemma 11mentioning
confidence: 99%
“…Both RIP [16][17][18][19] and coherence [9][10][11][12][13][20][21][22][23][24][25][26][27] are important tools to analyze the property of measurement matrices. In this paper, coherence will be adopted to analyze and illustrate the property of constructed measurement matrices, because it is easier to compute.…”
Section: Lemma 11mentioning
confidence: 99%
“…Similarly, Xu et al 28 developed methods to minimize the mutual coherence between the projection matrix and signal dictionary that leads to improved sparse recovery. Zhang et al 29 proposed a class of sparse binary sensing matrices based on the photograph LowDensity Parity-Check (LDPC) codes and analyzed recovery performance as a function of mutual coherence. In that work, it was shown that there is a direct correlation between low mutual coherence and the probably of exact recovery.…”
Section: Sensing Matrix Analyticsmentioning
confidence: 99%
“…Algebraic curves like elliptic curves can also be used to construct the deterministic measurement matrices [13]. LDPC code is another kind of method for constructing the deterministic measurement matrices [14]. All these methods only need to store some parameters rather than the whole matrix, but the measurement matrix has to be generated in real-time.…”
Section: Related Workmentioning
confidence: 99%
“…From (14) and (15), the low bound of one STP-CS key storage space is smaller than that of one traditional CS key storage space, when ̸ = 1. According to (4) and (5), is a column vector of dimension / .…”
Section: Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation